Is There a Correlation Between Dog Obesity and Human Obesity? Preliminary Findings of Overweight Status Among Dog Owners and Their Dogs - Linder, Deborah E.; Santiago, Sasha; Halbreich, Eli D. (Frontiers in Veterinary Science, 2021)
Background: Obesity is a serious health issue in people and their pets, with a need for innovative and engaging prevention strategies. One possible strategy is a One Health approach incorporating dogs into prevention programs; however, little data exist in the U.S. about the association between weight status among dog owners and their dogs. The objective of this study was to determine if there was an association between body mass index of adult dog owners and corresponding weight status in their dogs. Materials and Methods: This cross-sectional correlation study collected data from 38 adult dog owners aged 18 years and older and their dogs at three pet festivals throughout New England. Body mass index of dog owners and body condition scores of dogs were measured on site. Spearman correlation was used to compare weight status in dogs and their owners. Results: The median body mass index of dog owners was 25 (range of 17-52) and the median body condition score of dogs was 6 (range of 4-9). Frequency of overweight and obesity in dog owners was 31.6% and 26.3%, respectively, and 50.0% and 13.2% in dogs, also respectively. Owner body mass index was positively correlated with dog body condition score (r = 0.60, p < 0.001). Conclusion: Our findings support a possible association between overweight status in dogs and their owners. These findings could be leveraged in future interventions to promote healthier and more active lifestyles for both dog owners and their dogs in an engaging and innovative obesity prevention approach.